EFEKTIFITAS TEKNIK DISKUSI KELOMPOK DENGAN MODEL BLENDED LEARNING UNTUK MENCEGAH PROKRASTINASI AKADEMIK SISWA SMP - Ah. Fahri Munir; Riski Putra Ayu Distira; Nadlirun Nadiyya; Chyntia Intan Nuryana; Abdur Ro'uf Fajri (IKIP Siliwangi, 2026)
Academic procrastination is a behavior of delaying academic tasks, which can lead to several negative impacts, including excessive anxiety and high levels of stress. This study aims to determine the effectiveness of group discussion techniques in preventing academic procrastination among junior high school students. This research employs a quantitative pre-experimental method with a one-group pretest–posttest design. The subjects of this study consisted of 12 students selected using a purposive sampling technique. Research data collection was carried out using an academic procrastination scale that has been tested for validity and reliability. Data analysis was carried out using the Wilcoxon signed-rank test to identify changes before and after the treatment was administered. The results of the study indicate that there is a significant difference in scores before and after the implementation of the group discussion technique, with an Asymp. Sig. value for the pretest and posttest of 0.005, which is below 0.05. This suggests that the group discussion technique is effective in preventing academic procrastination. It can be concluded that research using group discussion techniques is effective in preventing academic procrastination in junior high school students.